2010
DOI: 10.1002/ddrr.107
|View full text |Cite
|
Sign up to set email alerts
|

Complex I disorders: Causes, mechanisms, and development of treatment strategies at the cellular level

Abstract: Mitochondrial oxidative phosphorylation (OXPHOS) represents the final step in the conversion of nutrients into cellular energy. Genetic defects in the OXPHOS system have an incidence between 1:5,000 and 1:10,000 live births. Inherited isolated deficiency of the first complex (CI) of this system, a multisubunit assembly of 45 different proteins, occurs most frequently and originates from mutations in either the nuclear DNA, encoding 38 structural subunits and several assembly factors, or the mitochondrial DNA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 65 publications
1
34
0
Order By: Relevance
“…Thus, complex I is essential for plant growth under natural conditions, and complex I mutants can only be maintained under benign growth conditions in the laboratory. This conclusion is in line with studies in mammals describing complex I as essential for growth (Valsecchi et al, 2010). However, we observed that once photosynthesis has been established, growth is no longer dependent on the application of external sugars and the mutants can complete their life cycle.…”
Section: Growth Phenotypes Of Complex I Mutantssupporting
confidence: 91%
“…Thus, complex I is essential for plant growth under natural conditions, and complex I mutants can only be maintained under benign growth conditions in the laboratory. This conclusion is in line with studies in mammals describing complex I as essential for growth (Valsecchi et al, 2010). However, we observed that once photosynthesis has been established, growth is no longer dependent on the application of external sugars and the mutants can complete their life cycle.…”
Section: Growth Phenotypes Of Complex I Mutantssupporting
confidence: 91%
“…[193]). Indeed, analysis of cells from patients with isolated CI deficiency, maximal CI enzymatic activity and the amount of fully-assembled CI (determined by native gel electrophoresis) proportionally declined [194]. However, mitochondrial content was not reduced in these cells [150], demonstrating that OXPHOS protein levels and Vmax values not always reflect mitochondrial content.…”
Section: Biochemical Biomarkersmentioning
confidence: 93%
“…Transgenic mouse models of mitochondrial disorders recently became available and significantly contributed to the demonstration that the pathogenesis of OXPHOS defects is not merely due to a deficiency in the production of adenosine triphosphate (ATP) within high energy-demand tissues [6]. Indeed, several reports demonstrate that ATP and phosphocreatine levels are not reduced in patient cells or tissues of mice bearing respiratory defects [7,8]. These findings, along with evidence that astrocyte and microglial activation takes place in the degenerating brain of mice with mitochondrial disorders [9], suggest that the pathogenesis of encephalopathy in mitochondrial patients is pleiotypic and more complex than previously envisaged.…”
Section: Introductionmentioning
confidence: 99%